2022
DOI: 10.24857/rgsa.v16n2-015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación comparativa entre el conocimiento empírico y científico sobre el uso de las plantas medicinales y sus compuestos

Abstract: Objective: to evaluate the empirical use of medicinal plants for the treatment of bacterial infections, compared to the theoretical-scientific foundations, according to the literature.   Theoretical framework: medicinal plants play a very important role in human history. Through empiricism, many lives were saved and in this process Science evolved, transforming popular knowledge into scientific fact. Resistance of microorganisms, especially bacteria, to conventional drugs is a recurring problem that can be sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
0
1
0
3
Order By: Relevance
“…Substâncias com principio ativo presentes nos vegetais podem fornecer ação antimicrobiana semelhante ao das substâncias sintéticas, o que pode minimizar o problema recorrente da resistência dos microrganismos, principalmente das bactérias, aos medicamentos convencionais (Bones et al, 2022).…”
Section: Teste De Diluição Em Caldounclassified
See 2 more Smart Citations
“…Substâncias com principio ativo presentes nos vegetais podem fornecer ação antimicrobiana semelhante ao das substâncias sintéticas, o que pode minimizar o problema recorrente da resistência dos microrganismos, principalmente das bactérias, aos medicamentos convencionais (Bones et al, 2022).…”
Section: Teste De Diluição Em Caldounclassified
“…As plantas apresentam uma variedade de metabólitos secundários, como terpenoides, alcaloides e flavonoides que apresentam as propriedades biológicas ou funcionais. Esses metabólitos secundários e outros compostos presentes nos extratos e no óleo essencial estão relacionados com o uso tradicional e popular de plantas medicinais e aromáticas, como no tratamento de sintomas infecciosos causados por bactérias (Bones et al, 2022). Devido à resistência de microrganismos à antibióticos normalmente usados, a pesquisa de novas substâncias com atividade antibacteriana é necessária.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The research was conducted in three Southern States (Rio Grande do Sul, Paraná, and Santa Catarina)to identify plants used in the treatment of bacterial diseases and compare them with scientific basis. Literature shows that the plant contains medicinal potential chemical components (Bones et al, 2022) A study of inhibition mechanism showed that flavonoids can targeting the bacterial membrane and cause damage to membrane integrity and biosynthesis. Besides it's a flavonoid work by inhibiting cell wall synthesis, inducing hydrolysis and preventing bacteria from synthesizing biofilms.…”
Section: Phytochemicals Constituent In M Oleifera Leaf Extractmentioning
confidence: 99%